Proyecto de factibilidad para la creación de un centro de terapia física (gimnasia) para adulto mayor en la ciudad de Quito - Castillo Torres, Jenny Lisseth (2015)
This project aims to develop a feasibility study for creating a physical therapy center (gym) for the elderly in the city of Quito, research was applied to the population Elderly in the city of Quito, so It was due to conduct a survey and a sample of it was obtained. The methodology used in this thesis project was the descriptive method, analytical, scientific and technical survey of the population is realized according to the INEC 2010 the total population of older adults in the city of Quito to seniors 65, was a total of 205,639 45% are men and 55% women, and then project the population by 2014, with a population growth rate of 9.2%; so it has a population of 292,413 seniors in the city of Quito. The results obtained in the study were of potential market demand, real demand and annual effective demand also offer services for 1'736.280 unmet demand for services for physical therapy centers for the elderly in this city It determined that the study is feasible to do so. With respect to the technical study determined that the installed capacity was 29,200 annual service with a capacity utilization of 75% for the first year of life of the project, the location of the investment project work in the field of Conception, Av .Emperor Charles V, between Calle Machala y Calle F. Espinoza. In regard to the organizational study, this will be a limited liability company whose corporate name will be physical therapy center for the elderly "THE LIGHT OF AN ANGEL", determining the hierarchical levels, the structural, functional and organizational positional governing for the functions of each of those who work in the company. The financial study found that need to invest in fixed assets, deferred assets and current assets in an amount of 92,012.06 dollars, giving a total investment will be provided by the partners of the company is 46% or 42,012, $ 06 and a bank loan of 54% that is $ 50,000.00. The financial evaluation, the result was 33667.46 NPV, IRR was 18.31%, the benefit-cost ratio was $ 1.49 which means that the company will receive 49 cents for every dollar invested, Recovery capital will be 5 years, 8 months and 19 days and finally the sensitivity analysis it was determined that the increase in costs is 21.6% and the decrease in income is 14.51% which means that the project is feasible to do so